Designing digital storytelling books for TPACK development of Indonesian pre-service ELT teachers - Signori, Tifani Yuris; Drajati, Nur Arifah; Putra, Kristian Adi (ELT Forum: Journal of English Language Teaching, 2024)
In today's educational system, the need for teachers to acquire technological, pedagogical, and content knowledge (TPACK) has already become a mainstream transformation. Therefore, it is necessary to find a suitable strategy and approach to develop pre-service ELT teachers’ TPACK, in which one of them is actively engaging them in the design of technology-enhanced learning. This study sought to investigate Indonesian pre-service ELT teachers’ TPACK level development after designing digital storytelling book. Narrative inquiry was adopted in this research. The data were obtained from the pre- service ELT teachers’ reflective notes and semi-structured interviews. The findings of the study show that all participants are in the TPACK level of “accepting”. In the level of accepting, pre-service teachers form a favorable attitude toward teaching and learning English with digital storytelling. The implication derived from this study is that it is necessary to carefully design a project in teacher education program that can improve the pre-service teachers' TPACK level.